Academic achievement among immigrant children in Irish primary schools - Frances McGinnity; Merike Darmody; Aisling Murray (The Economic and Social Research Institute (ESRI), 2015)
Educational achievement is a key indicator of labour market success and other post-school outcomes. This success is unequally distributed across different groups of children, including those from immigrant backgrounds. The impact of parents' and their children's cultural capital on student grades and educational ambitions has been identified in both longitudinal and cross-sectional studies. This paper addresses a gap in research on Ireland by exploring the academic achievement of 9-year-old immigrant children from different national groups using data from the child cohort of the Growing Up in Ireland study. The Irish case is interesting as there was recent substantial immigration of a nationally diverse group of migrants to a school system that was predominantly White, Catholic and Irish. The immigrant 'penalty' in English reading achievement varies across national groups, though overall the gap is modest. Financial strain is associated with lower reading achievement, as is attending a disadvantaged school, though these play a limited role in explaining the immigrant penalty in achievement. Social and cultural capital plays a more salient role in understanding national group differences in English reading achievement, particularly for East Europeans, for whom the gap is greatest.
Keywords: 330; Immigrant Children; Academic Achievement; Primary School; Growing Up In Ireland Data